## Question

`Evaluate: 11 + sqrt(-4 + 6 × 4 ÷ 3)`

`Evaluate: 11 + sqrt(-4 + 6 × 4 ÷ 3)`

A. 11

B. 13

C. 15

D. 27

**Answer: B. 13**

**Solution:**

According to order of operations, inner brackets first where 6 × 4 ÷ 3 is first calculated since it has a multiplication and a division.

6 × 4 ÷ 3

= 24 ÷ 3

= 8

Hence,

**11 + sqrt(-4 + 6 × 4 ÷ 3)**

= 11 + sqrt(-4 + 8)

= 11 + sqrt(4)

= 11 + 2

**= 13**

**Hence, The answer is 13.**

**Read more:**

Evaluate: -18 + 4(6 ÷ 2)^2 | Write 230,000,000,000 in scientific notation. |

If a + b = 3 and a^2 + b^2 = 7, what is a^4 + b^4? | If 2 + 2 = 6, 3 + 3 = 11, 4 + 4 = 18, what is the solution of 6 + 6 = ? |